Amino acid composition of pigeon pea varieties through HPTLC - Kirankumar P. Suthar; Diwakar Singh; Nitin B. Patel; Digvijay A. Chauhan; Rajkumar B. Katagi; Komal G. Lakhani (Vegetos, 2025)

Multifaceted Traits of Osmotic Stress Tolerance in Vigna Species: A Study of Section Aconitifoliae from India - Nitin T. Gore; Ganesh D. Mankar; Sumaiya S. Shaikh; Rajkumar B. Barmukh; Pankaj S. Mundada; Suraj D. Umdale; Gayacharan; Nikhil B. Gaikwad; Tukaram D. Nikam; Vitthal T. Barvkar; Mahendra L. Ahire (Journal of Crop Health, 2025)

Sustainable selenium ions adsorption of cyclodextrin and cellulose functionalized layered double hydroxide/reduced graphene oxide nanocomposites - V. Nithya Priya; M. Rajkumar; V. Rajendran; J. Mobika; S.P. Linto Sibi; B. Veena; V. Vijayalakshmi; P. Ahila (Journal of Water Process Engineering, 2025)

Evaluation of local finger millet (Eleusine coracana (L.) Gaertn.) landraces for salinity tolerance using growth and biochemical traits at the seedling stage - Sumaiya S. Shaikh; Nitin T. Gore; Ganesh D. Mankar; Rajkumar B. Barmukh; Pankaj S. Mundada; Suraj D. Umdale; Mahendra L. Ahire (Cereal Research Communications, 2024)

Seasonal variability of microplastic contamination in marine fishes of the state of Gujarat, India - Yagnesh B. Motivarash; Ashishkumar J. Bhatt; Rahul R. Jaiswar; Rehanavaz A. Makrani; Rajkumar M. Dabhi (Environmental Science and Pollution Research, 2024)

Euwallacea perbrevis (Schedl, 1951) and associated novel fungal symbiont, Fusarium sp.: A potential cause of wilting in cocoa, Theobroma cacao in India - Shivaji Hausrao Thube; R Thava Prakasa Pandian; M. Rajkumar; Merin Babu; A. Josephrajkumar; Santhoshkumar P; B.J. Nirmal Kumar; Vinayaka Hegde; Balanagouda Patil; H. Rajashekara; T. Prabhulinga; Babasaheb B. Fand; et al. (Crop Protection, 2024)

Effect of hybrid steel fibres on shear behaviour of self compacting RC beam - K. B. Ramkumar; C. Sudha; K. Gunasekaran; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Long-term tributyltin exposure alters behavior, oocyte maturation, and histomorphology of the ovary due to oxidative stress in adult zebrafish - Rajkumar S. Delvadiya; Urvesh D. Patel; Mihir R. Tank; Harshad B. Patel; Swati S. Patel; Bhavesh J. Trangadia (Reproductive Toxicology, 2024)

Studies on the concrete with composite cement and alccofine: from use of OPC towards low-carbon quaternary binder - B. Suresh; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

Agrosilvopastoral systems for improved crop and fodder productivity and soil health in the rainfed environments of South India - G. Venkatesh; K.A. Gopinath; D.B.V. Ramana; V. Visha Kumari; I. Srinivas; Arun K. Shanker; K.V. Rao; J.V.N.S. Prasad; K. Sammi Reddy; K.B. Sridhar; B. Sarkar; B.M.K. Raju; et al. (Agricultural Systems, 2024)

A Review on Pyrolysis of Agro-waste and Plastic Waste into Biofuels: Shifting to Bio-based Economy - Midhun Prasad K; Murugavelh Somasundaram; B Anand; R Shankar; Rajkumar P (BioEnergy Research, 2023)

Formation damage and improved recovery in kaolinitic high enthalpy gas fields with fabric geological settings - B. Kanimozhi; P. Rajkumar; S. Mahalingam; S. Senthil; D.S. Jayalakshmi; H. Girija Bai; Vivek Thamizhmani; Ramadoss Kesavakumar; Venkat Pranesh (Gas Science and Engineering, 2023)

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

Alpha-ketoglutarate supplementation and BiologicaL agE in middle-aged adults (ABLE)—intervention study protocol - Elena Sandalova; Jorming Goh; Zi Xiang Lim; Zhi Meng Lim; Diogo Barardo; Rajkumar Dorajoo; Brian K. Kennedy; Andrea B. Maier (GeroScience, 2023)
Targeting molecular processes of aging will enable people to live healthier and longer lives by preventing age-related diseases. Geroprotectors are compounds with the potential to increase healthspan and lifespan. Even though many of them have been tested in animal models, the translation to humans is limited. Alpha-Ketoglutarate (AKG) has been studied widely in model animals, but there are few studies testing its geroprotective properties in humans. ABLE is a double blinded placebo-controlled randomized trial (RCT) of 1 g sustained release Ca-AKG versus placebo for 6 months of intervention and 3 months follow up including 120 40–60-year-old healthy individuals with a higher DNA methylation age compared to their chronological age. The primary outcome is the decrease in DNA methylation age from baseline to the end of the intervention. A total of 120 participants will be randomized to receive either sustained release Ca-AKG or placebo. Secondary outcomes include changes in the inflammatory and metabolic parameters in blood, handgrip strength and leg extension strength, arterial stiffness, skin autofluorescence, and aerobic capacity from baseline to 3 months, 6 months, and 9 months. This study will recruit middle-aged participants with an older DNA methylation age compared to their chronological age, and test whether supplementation with Ca-AKG can reduce DNA methylation age. This study is unique in its inclusion of biologically older participants.

Correction to: Pollen staining is a rapid and cost‑effective alternative to marker‑assisted selection for recessive waxy1 gene governing high amylopectin in maize - Zahirul A. Talukder; Vignesh Muthusamy; Rajkumar U. Zunjare; Rashmi Chhabra; Shashidhar B. Reddappa; Subhra J. Mishra; Nitish R. Prakash; Nisrita Gain; Gulab Chand; Firoz Hossain (Physiology and Molecular Biology of Plants, 2022)

Economic feasibility of subsurface drainage (SSD) to control waterlogging and soil salinity under different scenarios in the Tungabhadra project command, Karnataka, India - Karegoudar A V; Vishwanath J; Rajkumar R H; Anand S R; Polisgowdar B S; Ayyanagowdar M S; Nemichandrapp M; Kaledhonkar M J (Irrigation and Drainage, 2022)
The Tungabhadra irrigation command area (TBP) in Karnataka, India, has three scenarios: the head, mid and tail reach command areas. The head reach has ample good quality canal water availability, and the mid reach area has limited canal water availability. In recent decades, rice–rice monocropping in vertisols, especially by these head and mid reach farmers, has led to not only water shortages but also the development of waterlogging and secondary soil salinization in the tail (lower) reach of the command due to seepage. As the soil salinity in the head reach was less severe, a slightly wider drain spacing of 60 m was adopted over 15 ha. In the case of the mid reach, salinity was slightly higher than the head reach but slightly less than the tail reach, hence 50 m drain spacing was laid out over 24 ha. Due to the slightly higher soil salinity at the tail end of the command, a closer drain spacing of 40 m was adopted over 11 ha. In all these scenarios, the drain depth was 1.0 m. Despite differences in irrigation water availability and different soil salinity conditions, the study clearly indicated over six seasons that the SSD system is a viable solution for the reclamation of waterlogged saline soils and enhancing rice productivity in all three scenarios of the TBP command.

Pollen staining is a rapid and cost-effective alternative to marker-assisted selection for recessive waxy1 gene governing high amylopectin in maize - Zahirul A. Talukder; Vignesh Muthusamy; Rajkumar U. Zunjare; Rashmi Chhabra; Shashidhar B. Reddappa; Subhra J. Mishra; Nitish R. Prakash; Nisrita Gain; Gulab Chand; Firoz Hossain (Physiology and Molecular Biology of Plants, 2022)

Biodiesel blends: a comprehensive systematic review on various constraints - Rajkumar Kamaraj; Yarrapragada K.S.S. Rao; Balakrishna B (Environmental Science and Pollution Research, 2022)

Water deficit-induced oxidative stress and differential response in antioxidant enzymes of tolerant and susceptible tea cultivars under field condition - M. Nalina; S. Saroja; M. Chakravarthi; R. Rajkumar; B. Radhakrishnan; K. N. Chandrashekara (Acta Physiologiae Plantarum, 2021)

Genetic analysis of growth and egg production traits in synthetic colored broiler female line using animal model - L. Leslie Leo Prince; K. S. Rajaravindra; U. Rajkumar; B. L. N. Reddy; C. Paswan; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2020)

A novel leaf rust resistance gene introgressed from Aegilops markgrafii maps on chromosome arm 2AS of wheat - K. Rani; B. R. Raghu; S. K. Jha; Priyanka Agarwal; Niharika Mallick; M. Niranjana; J. B. Sharma; A. K. Singh; N. K. Sharma; S. Rajkumar; S. M. S. Tomar; Vinod (Theoretical and Applied Genetics, 2020)

Effect of supplementing germinated sprouts of pulses on performance, carcass variables, immune and oxidative stress indicators in broiler chickens reared during tropical summer season - S. V. Rama Rao; B. Prakash; U. Rajkumar; M. V. L. N. Raju; T. Srilatha; E. P. K. Reddy (Tropical Animal Health and Production, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Grading of proximal internal carotid artery (ICA) stenosis by Doppler/duplex ultrasound (DUS) and computed tomographic angiography (CTA): correlation and interrater reliability in real-life practice - Oliver Matz; Omid Nikoubashman; Parajuli Rajkumar; Andreas Keuler; Martin Wiesmann; Jörg B. Schulz; Arno Reich (Acta Neurologica Belgica, 2017)

Identification and agro-morphological characterization of rice genotypes resistant to sheath blight - Susmita Dey; Jyothi Badri; V. Prakasam; V. P. Bhadana; K. B. Eswari; G. S. Laha; C. Priyanka; Aku Rajkumar; T. Ram (Australasian Plant Pathology, 2016)

Response of upland cotton (G.hirsutum L.) genotypes to drought stress using drought tolerance indices - Chandrakant Singh; Vijay Kumar; Indivar Prasad; Vishal R. Patil; B. K. Rajkumar (Journal of Crop Science and Biotechnology, 2016)

Predicting Irrigated and Rainfed Rice Yield Under Projected Climate Change Scenarios in the Eastern Region of India - A. V. M. Subba Rao; Arun K. Shanker; V. U. M. Rao; V. Narsimha Rao; A. K. Singh; Pragyan Kumari; C. B. Singh; Praveen Kumar Verma; P. Vijaya Kumar; B. Bapuji Rao; Rajkumar Dhakar; M. A. Sarath Chandran; et al. (Environmental Modeling & Assessment, 2016)

Molecular diversity of Bipolaris oryzae infecting Oryza sativa in India - A. Kandan; J. Akhtar; B. Singh; D. Dixit; D. Chand; A. Roy; S. Rajkumar; P. C. Agarwal (Phytoparasitica, 2015)

Molecular mapping of genomic regions harbouring QTLs for root and yield traits in sorghum (Sorghum bicolor L. Moench) - Rajkumar; B. Fakrudin; S. P. Kavil; Y. Girma; S. S. Arun; D. Dadakhalandar; B. H. Gurusiddesh; A. M. Patil; M. Thudi; S. B. Bhairappanavar; Y. D. Narayana; P. U. Krishnaraj; et al. (Physiology and Molecular Biology of Plants, 2013)

Outcome definitions and clinical predictors influence pharmacogenetic associations between HTR3A gene polymorphisms and response to clozapine in patients with schizophrenia - A. P. Rajkumar; B. Poonkuzhali; A. Kuruvilla; A. Srivastava; M. Jacob; K. S. Jacob (Psychopharmacology, 2012)

Cx43, ZO-1, alpha-catenin and beta-catenin in cataractous lens epithelial cells - Anshul I Arora; Kaid Johar; Devarshi U Gajjar; Darshini A Ganatra; Forum B Kayastha; Anuradha K Pal; Alpesh R Patel; S Rajkumar; Abhay R Vasavada (Journal of Biosciences, 2012)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

New discovery of coral rubbings in the north-western Gulf of Kachchh, Gujarat, Western India — GIS based evaluation - J. Sesh Serebiah; M. Rajkumar; Jun Sun; B. A. Venmathi Maran; A. Saravanakumar; G. A. Thivakaran (Journal of Ocean University of China, 2011)

Polymorphism in the Prolactin Promoter and Its Association with Growth Traits in Chickens - T. K. Bhattacharya; R. N. Chatterjee; R. P. Sharma; M. Niranjan; U. Rajkumar; B. L. N. Reddy (Biochemical Genetics, 2011)

AFLP-Based Genetic Diversity Assessment of Commercially Important Tea Germplasm in India - R. K. Sharma; M. S. Negi; S. Sharma; P. Bhardwaj; R. Kumar; E. Bhattachrya; S. B. Tripathi; D. Vijayan; A. R. Baruah; S. C. Das; B. Bera; R. Rajkumar; et al. (Biochemical Genetics, 2010)

A Common Transport System for Methionine, l-methionine-dl-Sulfoximine (MSX), and Phosphinothricin (PPT) in the Diazotrophic Cyanobacterium Nostoc muscorum - Arvind Kumar Singh; Mayashree B. Syiem; Rajkumar S. Singh; Samrat Adhikari; Amar Nath Rai (Current Microbiology, 2008)

Molecular mapping of genomic regions harboring QTLs for stalk rot resistance in sorghum - P. Srinivasa Reddy; B. Fakrudin; Rajkumar; S. M. Punnuri; S. S. Arun; M. S. Kuruvinashetti; I. K. Das; N. Seetharama (Euphytica, 2008)

Identification of two RAPD markers genetically linked to a recessive allele of a Fusarium wilt resistance gene in pigeonpea (Cajanus cajan L. Millsp.) - H. Kotresh; B. Fakrudin; S. M. Punnuri; B. K. Rajkumar; M. Thudi; H. Paramesh; H. Lohithswa; M. S. Kuruvinashetti (Euphytica, 2006)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)